2023
DOI: 10.3389/fnagi.2023.1131979
|View full text |Cite
|
Sign up to set email alerts
|

The association between stress, emotional states, and tinnitus: a mini-review

Abstract: Extensive literature supporting the view of tinnitus induced stress in patients is available. However, limited evidence has been produced studying the opposite, that is, does stress cause tinnitus? The hypothalamus pituitary adrenal axis, one of the main neuroendocrine systems involved in stress response, is commonly disturbed in tinnitus patients. Patients with chronic tinnitus have been shown to develop abnormal responses to psycho-social stress, where the hypothalamus pituitary adrenal axis response is weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 92 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Pre-vaccination psychological health as a risk factor has not been considered in our survey. Stress, anxiety and depression have been associated with risk of tinnitus ( Patil, Alrashid, Eltabbakh and Fredericks, 2023 ). The social distancing-related stress and emotional impact could contribute to the risk of COVID-19 vaccination-related tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-vaccination psychological health as a risk factor has not been considered in our survey. Stress, anxiety and depression have been associated with risk of tinnitus ( Patil, Alrashid, Eltabbakh and Fredericks, 2023 ). The social distancing-related stress and emotional impact could contribute to the risk of COVID-19 vaccination-related tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic and its requirements for isolation have introduced significant additional stress into the lives of individuals worldwide. Given the established link between tinnitus and stress [36], it is reasonable to expect that there would have been a negative impact on tinnitus sufferers at this time. The potential effect of COVID-19 infection on hearing loss adds another layer of complexity.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of misophonia, the common pathway might be the mechanism, which generates the aversive character of specific sounds [ 89 , 90 ], whereas in phonophobia, fear of loud sounds is the common denominator [ 90 ]. Some, but not all, studies [ 91 , 92 ] suggest an increased risk of arterial hypertension among tinnitus patients, which might be an indicator of increased sympathetic activation, which is in keeping with stress as modulating tinnitus [ 46 , 50 , 93 ].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Imaging studies have shown that tinnitus reduction via distraction is related to reduced neuronal activity in the auditory cortex [ 115 ]. Some patients report that the intensity of tinnitus increases in stressful situations [ 49 , 93 ]. This can be explained by a general enhancement of alertness to sensory signals under sympathetic activation.…”
Section: Tinnitus Modifying Factorsmentioning
confidence: 99%